Paternalistic Management and Technology, a Complex Choice. the Coal and Industrial Company of Lota (1920-1940) [Gestión Paternalista y Tecnología, Una Elección Compleja. la Compañía Carbonífera E Industrial de Lota (1920-1940)] - Venegas-Valdebenito, H; Morales-Barrientos, D (Universidad de Tarapaca, 2019)
This article analyzes the design and some results of the "paternalist model" in the Mining and Industrial Company of Chile. According to this objective, variables such as output and productivity are analyzed. The article also describes the traditional work done by "barretros", or miner whose working tool was the crow bar. The article also examines the limitations and eventual collapse of the "paternalists model". © 2019 Universidad de Tarapaca.